A New Proanthocyanidins from Arbutus unedoL. Stems - DIB, M.A.; ALLALI, H.; TABTI, B.; BENDIABDELLAH, A.; DJABOU, N. (Asian Journal of Chemistry, 2010)
Proanthocyanidins extraction using a water/methanol/ acetone mixture of the Arbutus unedo L. was followed by structural study, indicating the presence of (+)-catechin, (+)- afzelechin and of the unknown (3,4-dihydroxy-phenyl)-5,7- dihydroxychroman-3-yl 4-hydroxybenzoate.